2022
DOI: 10.2147/ndt.s387063
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with Bipolar Disorder Have a Higher Level of Homocysteine Than Major Depressive Disorder: A Retrospective Chart Review and Observational Study

Abstract: Purpose Previous studies suggest that homocysteine (Hcy) may be involved in the pathogenesis of bipolar disorder (BD) and major depressive disorder (MDD) by influencing glutamatergic transmission, inflammation, and other mechanisms. There are no established biomarkers to distinguish BD from MDD. This study aims to compare Hcy levels between BD and MDD. Patients and Methods We collected medical records of patients aged 14–75 admitted to the hospital from January 1 to Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…For example, distinct gut microbial compositions were identified in MDD patients compared to BD patients ( 30 ). Homocysteine levels were elevated in MDD and BD patients, and were higher in BD patients than in MDD patients ( 31 ). The resting state functional magnetic resonance imaging (fMRI) studies revealed that BD patients had a specific increased amplitude of low frequency fluctuations in the right brain regions and bilateral cerebellum ( 32 , 33 ), while specific abnormalities were found in functional connectivity in the amygdala-ventral PFC in MDD ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, distinct gut microbial compositions were identified in MDD patients compared to BD patients ( 30 ). Homocysteine levels were elevated in MDD and BD patients, and were higher in BD patients than in MDD patients ( 31 ). The resting state functional magnetic resonance imaging (fMRI) studies revealed that BD patients had a specific increased amplitude of low frequency fluctuations in the right brain regions and bilateral cerebellum ( 32 , 33 ), while specific abnormalities were found in functional connectivity in the amygdala-ventral PFC in MDD ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, HCY has gained extensive attention. According to epidemiologic data, HCY is strongly correlated with the prognosis of cardiovascular disease and serves as an independent risk factor for the condition ( 6 ). Further research is required to determine whether elevated HCY levels are associated with an increased risk of major adverse cerebrocardiovascular events (MACCEs) in individuals with OSAHS.…”
Section: Introductionmentioning
confidence: 99%